Pengaruh Laporan Keberlanjutan dan Akuntansi Hijau Terhadap Kinerja Keuangan ada Perusahaan Manufaktur Sektor Aneka Industri Yang Terdaftar di BEI - Veni Marisa Aniza; Saring Suhendro (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to examine the effect of sustainability reports, proxied by corporate social responsibility, and green accounting, proxied by the PROPER index, on financial performance, with company size as a control variable. The population in this study were manufacturing companies in various industrial sectors listed on the Indonesia Stock Exchange for the 2020-2024 period. A purposive sampling method was used to obtain the research sample. The company's official website, the Indonesia Stock Exchange, and the Ministry of Environment and Forestry were used to obtain sustainability reports and green accounting data. The analysis technique used was multiple linear regression. The results showed that sustainability reports had a significant positive effect on financial performance. Meanwhile, green accounting and company size had a positive but insignificant effect on financial performance